(untitled) (Journal of the College of Basic Education, 2022)
New bidentate mannich base having nitrogen and oxygen atom was prepared by condensation of the formaldehyde with piperidine and 8-hydroxyquinoline in ethanol. An ethanolic solution of the prepared ligand was reacted with an ethanolic solution of metal ions Cr(III ), Fe(III), Co(II) , Ni(II) and Cu(II) to give new complexes. All the prepared compounds were isolated and characterized by their melting points, FTIR and UV-Vis.,spectroscopy. Elemental analyses have been performed using C, H , N and atomic absorption technique , and the magnetic susceptibility have also been measured.